Professional and public accreditation as a management mechanism tool of socio-economic processes in the field of additional professional education - I. I. Deren; K. A. Erina (Вестник университета, 2023)
The article is devoted to the system analysis of organizations implementing programs of additional professional education as an element of the continuing education system in the Russian Federation. The article purpose is to determine the role of the professional public accreditation procedure in the management system of socio-economic processes in the field of additional professional education. According to the results of the study, the authors concluded that, having additional socio-economic effects, the procedure of the mandatory system of professional and public accreditation of organizations in the field of additional professional education can serve as one of the tools for the development of the educational activity management mechanism. The methodology of the research includes methods of analysis and synthesis, comparative method of cognition, methods of processing statistical information. The results of the study are valuable in developing a development strategy in the field of professional retraining and advanced training of employees from the state and commercial spheres.